Strata+Hadoop world : London complete video compilation - O'Reilly Media, Inc (O'Reilly Media, 2015)
"How are large businesses using data? What happens when data from the Internet of Things starts flowing in earnest? Find out with this complete video compilation of the Strata Conference + Hadoop World Conference in London during May 2015. You'll be front-row center for every presentation, whether it's a keynote, a tutorial, or a workshop."--Resource description page.